Penerapan Strategi Manajemen SDM terhadap Mutu Pelayanan di Politeknik Piksi Input Serang - Yanto Heryanto; Abdul Muhit; Dian Evariana; Abdi Ramdan (Kampus Akademik Publiser, 2023)
This study aims to analyze the implementation of human resource management (HRM) strategies in improving service quality at Politeknik Piksi Input Serang. In the context of vocational higher education institutions, excellent service is a key indicator of institutional performance, particularly in client-facing services such as academic publishing. This research employs a descriptive qualitative approach with data collected through in-depth interviews, observation, and documentation. The findings indicate that HRM strategies are implemented through a combination of on-the-job training (such as job rotation, internal coaching, mentoring, and seminars) and off-the-job training (including case studies, external training, and formal education advancement). These strategies significantly contribute to enhancing employees’ competencies, professionalism, and service delivery. Furthermore, the study reveals that structured and continuous HR development programs improve client satisfaction, reduce complaints, and strengthen the institution's public image as a responsive and competent vocational institution. Therefore, effective HRM strategies serve as a vital foundation for building service excellence in higher education institutions.